Role of Electrostatic Hotspots in the Selectivity of Complement Control Proteins Toward Human and Bovine Complement Inhibition - Narkhede, Yogesh B.; Gautam, Avneesh K.; Hsu, Rohaine V.; Rodriguez, Wilson; Zewde, Nehemiah T.; Harrison, Reed E. S.; Arantes, Pablo R.; Gaieb, Zied; Gorham, Ronald D.; Kieslich, Chris; Morikis, Dimitrios; Sahu, Arvind; et al. (Frontiers in Molecular Biosciences, 2021)
Poxviruses are highly dangerous pathogens, which can cause fatal infection in unvaccinated individuals. The causative agent of smallpox in humans, variola virus, is closely related to the bovine vaccinia virus, yet the molecular basis of their selectivity is currently incompletely understood. Here, we examine the role of the electrostatics in the selectivity of the smallpox protein SPICE and vaccinia protein VCP toward the human and bovine complement protein C3b, a key component of the complement immune response. Electrostatic calculations, in-silico alanine-scan and electrostatic hotspot analysis, as introduced by Kieslich and Morikis (PLoS Comput. Biol. 2012), are used to assess the electrostatic complementarity and to identify sites resistant to local perturbation where the electrostatic potential is likely to be evolutionary conserved. The calculations suggest that the bovine C3b is electrostatically prone to selectively bind its VCP exogenous ligand. On the other hand, the human isoform of C3b exhibits a lower electrostatic complementarity toward its SPICE ligand. Yet, the human C3b displays a highly preserved electrostatic core, which suggests that this isoform could be less selective in binding different ligands like SPICE and the endogenous human Factor H. This is supported by experimental cofactor activity assays revealing that the human C3b is prone to bind both SPICE and Factor H, which exhibit diverse electrostatic properties. Additional investigations considering mutants of SPICE and VCP that revert their selectivity reveal an “electrostatic switch” into the central modules of the ligands, supporting the critical role of the electrostatics in the selectivity. Taken together, these evidences provide insights into the selectivity mechanism of the complement regulator proteins encoded by the variola and vaccinia viruses to circumvent the complement immunity and exert their pathogenic action. These fundamental aspects are valuable for the development of novel vaccines and therapeutic strategies.